Artificial Intelligence and Curriculum Prospects for Elementary School - Rathore, Aamir Ali; Sultana , Nayyar; Zareen , Syed Jawad; Ahmed , Adeel (Pakistan Journal of Humanities and Social Sciences, 2023)
The research aims to investigate Artificial Intelligence (AI) and curriculum prospects for elementary school education. The study focused on identifying specific areas within curriculum where AI can be incorporated and assessed the prospects of AI which may enhance leaning experiences for elementary school students. Descriptive research design was used. Quantitative approach adopted for data collection. There were 70 participants including school leadership and teachers from elementary schools by using convenient sampling. AI and curriculum are interdependent variables. The study showed that the broad thoughtful opportunities and challenges associated with AI in elementary education. Results of the depicted that majority of the respondents agreed with the idea of introducing AI into curriculum which is helpful for the literacy of AI education. Results reflected that curriculum modification are needed continuously according to need of modern era. AI can monitor the usefulness of curriculum and identify specific areas. AI made a significant addition in optimization of contents, teaching methods and facilitates multimodal teaching style to increase the creativity, and innovation and problem solving skills. AI education in elementary school curriculum can better train students for 21st century and increase job opportunities for students through AI and technology integration in education.